The college writer : a guide to thinking, writing and researching - VanderMey, Randall (Boston : Houghton Mifflin, 2004)
The College Writer is a rhetoric, reader, research guide, and handbook that offers streamlined, nuts-and-bolts writing instruction.
Includes index.
Keywords: English language -- Rhetoric; Report writing